2019
DOI: 10.1002/jor.24071
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis related to functional outcome in patients operated for ankle fractures

Abstract: Ankle fractures are among the most common lower limb fractures. Associations between postoperative radiographic results and clinical outcome have been found, but less is known about the relevant ankle biomechanics. This study analysed ankle kinematics, radiographic findings and patient-reported outcome measures (PROM) in patients treated for ankle fractures. The hypothesis was that patients after ankle fracture surgery had less flexion/extension in the ankle compared to healthy subjects and that fracture sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Previous studies already showed a restriction of clinical dorsiflexion and plantarflexion between the tibia and the hindfoot in the stance and swing phase in affected patients compared to healthy participants [ 1 , 7 , 25 ]. This is in line with our results of restricted movement in the tibio-talar joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies already showed a restriction of clinical dorsiflexion and plantarflexion between the tibia and the hindfoot in the stance and swing phase in affected patients compared to healthy participants [ 1 , 7 , 25 ]. This is in line with our results of restricted movement in the tibio-talar joint.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we were able to show that these results are the same regardless of the foot model applied. While Wang et al [ 1 ] and van Hoeve et al [ 7 ] used the Oxford foot model or a modified version of it with just 3 segments for their examinations we used the HFMM. When comparing the results, one has to consider that the HFMM takes the independent movements of the tibio-talar and subtalar joint into account, while the Oxford foot model imagines these two just as a ball-and-socket joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are no sEMG frequency analysis studies in walking with perturbations, the sample size was chosen to be comparable with sEMG frequency analysis studies during walking with no perturbations using similar outcomes (Nüesch et al, 2012;Roeder et al, 2020;Zhang et al, 2017). Exclusion criteria included conditions effecting balance control such as: age over 65 (L. Sturnieks et al, 2008); obesity (i.e., body mass index [kg/m 2 ] > 30) (Kopelman, 2000); orthopedic conditions affecting gait and balance (e.g., total knee replacement, total hip replacement, ankle sprain, limb fracture in the period of one year prior to participation (Jansen et al, 2013;Kubota et al, 2013Kubota et al, , 2012van Hoeve et al, 2019)); neurological diseases associated with loss of balance (e.g., multiple sclerosis, myelopathy); and conditions that could affect adherence and participation such as: cognitive loss or psychiatric conditions; untreated cardiac conditions (e.g., non-stable ischemic heart disease, congestive heart failure); and chronic obstructive pulmonary disease . The study protocol was approved by the Institutional Review Board of Sheba Medical Center).…”
Section: Participantsmentioning
confidence: 99%
“…Ankle fractures are among the most common lower limb fractures and account for 9% of all fractures. 1 With the mechanism of injury varying from a simple fall to high-energy motor vehicle accidents, ankle fractures present a wide spectrum of fracture patterns. Ankle fractures are initially evaluated by physical examination and then by X-ray.…”
Section: Introductionmentioning
confidence: 99%